Structural elucidation of a novel polysaccharide from Ophiopogonis Radix and its self-assembly mechanism in aqueous solution. (15th February 2023) - Wang, Bei; Huang, Bin; Yang, Bing; Ye, Liang; Zeng, Jingqi; Xiong, Zhiwei; Chen, Yaping; Guo, Shuchen; Yang, Yanjun; Ma, Weikun; Zhu, Maomao; Jia, Xiaobin; et al.
Highlights: A new polysaccharide ORP-1 was isolated from Ophiopogonis Radix. ORP-1 mainly consisted of 2, 6-linked-Fru f and 1-linked-Glc p with Mw of 3667 Da. ORP-1 could self-assembled to form colloidal aggregate in water verified by MDS. Hydrogen bonds and hydrophobic interaction were the two main driving forces. ORP-1 with antioxidant activity can increase the water solubility of components. Abstract: Ophiopogonis Radix polysaccharides with various bioactivities have caught people's attention in the pharmaceutical and functional food industries. It is necessary to reveal their structures, chain conformations, and solvent behaviors. A neutral polysaccharide named ORP-1 with molecular weight of 3667 Da was obtained from Ophiopogonis Radix. It was composed of d -fructofuranose and d -glucopyranose in the ratio of 0.85:0.15. Methylation, FT-IR and NMR analysis indicated ORP-1 consisted of 2, 6-linked-Fru f units as the main chain and 1-linked-Glc p residue at the end. Congo red assay showed ORP-1 had no triple-helix structure. The observation of TEM and AFM found ORP-1 could self-assemble to form colloidal aggregate in water. This phenomenon was verified using CMC determination and MD simulation. Furthermore, intermolecular hydrogen bonds and hydrophobic interactions would be the main forces driving the aggregate. These results provided reference for the study of the chain conformation and behavior of polysaccharides in aqueous solution.